Aristophanes and Athenian society of the early fourth century B.C. - David, E. (Mnemosyne, Supplements, 1984)
The purposes of this short monograph are to identify and analyze the problems of Athenian society with which the last two extant plays of Aristophanes - the Ekklesiazousai and the Ploutos - are concerned, as well as to examine the playright's views on the essence of these problems and on attempts to find satisfactory solutions to them. The work contains an introduction and seven sections: 1. Historical Background; 2. Poverty: Symptoms, Ideas regarding Solutions and Criticisms of Ideas; 3. Poverty versus Riches; 4. The sources of the ''Communistic'' Ideas; 5. Misthos Ekklesiastikos ; 6. The Censure of Materialism; 7. Aristophanes and the ''Middle Road''. The author has attempted here to set forth both the value of Aristophanes' last plays as historical sources and the significance of their social message.